MAKNA HIDUP PRIA HOMOSEKSUALdi KOTA BANDA ACEH : SEBUAH STUDI KASUS - Mursal Sidiq; Dahlia Dahlia; Maya Khairani (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2013)
The purpose of this study is to understand the meaning of life among homosexuals men who live in Banda Aceh. This study used the qualitative method with a phenomenological approach. The participants of this study were three homosexual men. Data were collected using interviews and non-participant observation about 2 months. The result showed that homosexuals men found their meaning of life after becoming a gay because they had found the answer of their sexual orientation and self identity which brought them to happiness. The first and third participant found their meaning of life by sharing their life experience and supporting their homosexualmates who have the same problem related to their sexual identity. The second participant found his meaning of life by foundingYCommunity as a place to support those who are being a part of the homosexual communityand became an activist for LGBT (Lesbian, Gay, Bisexual, and Transgender) encounteringtheir sexuality and gender rights issues.